1997
DOI: 10.1097/00000658-199710000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Life Support for 100 Adult Patients With Severe Respiratory Failure

Abstract: ObjectiveThe authors retrospectively reviewed their experience with extracorporeal life support (ECLS) in 100 adult patients with severe respiratory failure (ARF) to define techniques, characterize its efficacy and utilization, and determine predictors of outcome. Summary Background DataExtracorporeal life support maintains gas exchange during ARF, providing diseased lungs an optimal environment in which to heal. Extracorporeal life support has been successful in the treatment of respiratory failure in infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
133
0
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(141 citation statements)
references
References 36 publications
2
133
0
6
Order By: Relevance
“…Knight et al reported a lower mean percutaneous oxygen saturation in the venovenous ECMO but a higher intravascular thrombosis in the venoarterial ECMO system, while others reported frequent bleeding complication in venoarterial ECMO. 1,2) A study by Stohr, et al suggested a lower mortality rate in patients treated with venovenoarterial ECMO than in patients treated with venovenous or venoarterial ECMO. 3) Furthermore, Lazar, et al reported successful usage of bicaval dual-lumen catheter in neonates while Bonacchi, et al reported an "X-configuration" system for veno-venous bypass by the use of a self-modified inflow cannula.…”
Section: Discussionmentioning
confidence: 99%
“…Knight et al reported a lower mean percutaneous oxygen saturation in the venovenous ECMO but a higher intravascular thrombosis in the venoarterial ECMO system, while others reported frequent bleeding complication in venoarterial ECMO. 1,2) A study by Stohr, et al suggested a lower mortality rate in patients treated with venovenoarterial ECMO than in patients treated with venovenous or venoarterial ECMO. 3) Furthermore, Lazar, et al reported successful usage of bicaval dual-lumen catheter in neonates while Bonacchi, et al reported an "X-configuration" system for veno-venous bypass by the use of a self-modified inflow cannula.…”
Section: Discussionmentioning
confidence: 99%
“…Existen algunos criterios para decidir la conexión a ECLS (cortocircuito intrapulmonar >30% con FiO 2 >0,6, distensibilidad <0,5 ml/cmH 2 O/kg, hipercarbia incorregible con pH <7,0 y presión inspiratoria pico >40 cmH 2 O), sin embargo, el juicio clínico y el análisis caso a caso pueden influir en la decisión. En adultos, esta técnica no ha tenido la eficacia que ha mostrado en el escenario neonatal, sin embargo, siempre debe ser considerada como una herramienta más en pacientes cuya mortalidad estimada es mayor a 70% y poseen una probabilidad razonable de recuperación pulmonar 1,13,14 . El ECLS ofrece dos formas básicas de soporte: veno-venoso (ECLS/V-V) cuando el circuito se origina y termina en el compartimiento venoso y veno-arterial (ECLS/V-A) cuando se inicia en el lecho venoso y termina en el arterial 1,2,7 .…”
Section: Discussionunclassified
“…Los mejores resultados obtenidos con el uso de ECLS en los últimos años, se relacionan con el perfeccionamiento de la técnica y modificación de los criterios de selección de los pacientes 14 . Entre ellos destaca la implementación precoz del ECLS, es decir, antes que se instale el daño pulmonar inducido por ventilación mecánica 19 .…”
Section: Discussionunclassified
“…This is because of increased cost and logistics but also because of disappointing results from the two previous randomized trials. 4,5 There has been renewed interest in adult ECMO due to encouraging results from case series, 6,7 improved ECMO technology, 2 general advances in critical care, 3,8 and, most recently, the use of ECMO in H1N1 patients. 9,10 In fact, CESAR was published electronically in the same month period as a retrospective case review of ECMO in adult respiratory failure 11 and a meta-analysis of ECMO following adult cardiac arrest.…”
Section: Critical Appraisalmentioning
confidence: 99%